The Differential Impact of Early Father and Mother Involvement on Later Student Achievement - McBride, Brent A. (J Educ Psychol, 2009)
The purpose of this exploratory study was to examine the direct and indirect effects of early parenting on later parental school involvement and student achievement. The sample, pulled from the first and second waves of the Panel Study of Income Dynamics – Child Development Supplement data set, consisted of 390 children ages 2–5 at time 1 and their families. Fathers’ and mothers’ participation in five dimensions of early parenting behaviors were assessed at time 1, while later parental school involvement and student achievement were assessed at time 2. Although early paternal and maternal parenting behaviors were not directly related to later student achievement, differences were revealed in the pattern of relationships between early parenting and later parental school involvement for fathers and mothers. In addition, fathers’ later school involvement was found to be negatively related to student achievement while maternal school involvement was found to be positively related to student achievement. These findings provide partial support for the hypothesized differential relationship between fathers’ and mothers’ early parenting and later student achievement.